Stone tools, techniques, and spaces for the pottery chaîne opératoire: the case of the pottery workshop of Gird-i Bazar (c. 1200-800 BC) in the Autonomous region of Kurdistan, Iraq - Squitieri, Andrea; Herrenschwand, Jean Jacques; Amicone, Silvia (Journal of anthropological archaeology, 2022)
Although the chaîne opératoire approach was introduced more than half a century ago, it has seldom been employed to reconstruct the techniques and tools involved in the production of Iron Age pottery (c. 1200–600 BC) from Iraqi Kurdistan. One of the reasons why this method is so seldomly applied is that only rarely can archaeologists rely on enough contextual information to allow the reconstruction of the specific steps of the pottery production and make inferences about the involvement of specific tools during these stages. In this paper, we present the case study of Gird-i Bazar, an Iron Age site located in Iraqi Kurdistan, where a pottery workshop yielding fixed installations and associated portable stone tools was recently discovered. We will combine context description and macro/microscopic observations on both stone tools and pottery sherds in order to show how the former were used in some of the steps of the pottery chaîne opératoire, and identify the spaces where specific stages of the pottery production possibly occurred. The results from this work will provide comparative material for the technological study of Iron Age pottery from Iraqi Kurdistan and its neighbouring regions in both lowland Mesopotamia and the western Iranian highlands.
Gesehen am 13.02.2023